Science-religion dialogue in education: religion teachers’ perceptions in a roman-catholic context - Paiva, J. C. (2021)
This paper examines the relationship between science and religion in the education system of Roman-Catholic Portuguese society. In particular, we explored perceptions of the relationship between science and religion for religious education teachers. We surveyed 198 Portuguese religious education teachers about how they view science and religion. The questionnaires’ results revealed a number of similarities: religious education teachers are highly involved in religious practices and exposed to science; they perceived a compatibility between science and religion; and they have an openness to dialogue between both. They do not adhere to anti-scientific perspectives, but they simultaneously try to limit what can be explained by science. Thus, an interpretative view of dialogue and/or integration seems to best explain the perceptions of religious education teachers of the relationship between science and religion. These findings allow a space of discussion, enabling teachers to possibly foster the science-religion dialogue in their contexts of pedagogical activity.